Ionic‐Liquid‐Modified Porous Au/CeMnOx Nanorods for Methyl Methacrylate (MMA) Synthesis via Direct Oxidative Esterification. Issue 11 (27th September 2019) - Tian, Yun; Li, Yuchao; Zuo, Cuncun; Yin, Defeng; Wang, Ling; Zheng, Yanxia; Huang, Haofei; Fu, Zhongjun; Wang, Ming
Abstract: Porous MnCeOx solid solutions nanorods (PN‐MnCeOx ) with different pore sizes were prepared using different carbon chain lengths ionic liquids (C10 mimCl, C12 mimCl and C14 mimCl). Series of novel catalysts with nano‐Au supported on the PN‐MnCeOx, were synthesized and applied to oxidative esterification of aldehydes (benzaldehyde derivatives or methacrolein – MAL) to esters. Catalytic performance was evaluated in batch reactor and the relatively optimum catalyst was screened out. Kinds of characterization methods, such as XRD, TEM, XPS and BET, were applied to analyze crystal plane, microstructure, specific surface area, and porous structure of the catalysts and the structure‐activity relationship could be reasonably explained. The cyclic stability of the catalyst was also tested more than 7 times using MAL and methanol for methyl methacrylate synthesis via one step oxidative esterification. Abstract : Catalysts made of Au nanoparticles on porous MnCeOx solid solutions nanorods were prepared by a hydrothermal method with different ionic liquids. Screening was performed to determine the optimal catalyst (Au/PNCM‐12) for one step oxidative esterification. Au/PNCM‐12 was then successfully applied in the oxidative esterification of methacrolein for methyl methacrylate synthesis with outstanding activities (conversion: 98.0%, selectivity: 82%) and excellent stability.